Influence of water soaking on swelling and microcharacteristics of coal. Issue 1 (20th October 2019) - Wen, Guangcai; Yang, Shuo; Liu, Yanbao; Wu, Wenbin; Sun, Dongling; Wang, Kai
Abstract: Improving the coal seam permeability is an important measure for increasing the coal bed methane (CBM) production and preventing gas disasters. Hydraulic technologies are effective ways of improving coal seam permeability. However, hydraulic technologies can also cause water to enter the coal seam, allowing the coal seam to soak for a long time. In this study, to obtain the influence of water soaking on the microscopic characteristics of coal, X‐ray diffraction (XRD), scanning electron microscopy (SEM), free swelling ratio tests, and low‐temperature nitrogen adsorption tests (LT‐NATs) were conducted. The mineral compositions of raw coal samples, the variation regularities of micromorphologies, and pore characteristics of the samples with different soaking times were obtained. The results showed that the coal samples contained about 8.5% clay minerals, of which 71% were illite/smectite mixed‐layer. Expansions of different sizes in the areas where the surface of the soaked coal samples contained clay minerals were observed, and the swelling was also observed macroscopically. The swelling not only led to an increase in the coal sample volume but also led to a decrease in pore volume. This change was magnified with the increase in soaking time (within 30 days). The cumulative pore volume of the samples soaked for 30 days was 0.00681 cm 3 /g. This was a reduction of 29.9% compared to the unsoaked samples. Moreover, the pore volumes show a logarithmic dependence on soaking time. This study provides evidence that the coal containing clay minerals will swell obviously when soaked in water, and the hydration swelling of clay minerals has a great influence on the swelling of coal. This swelling would lead to a decrease in the pore volume and the efficiency of CBM transport, thus affecting the effect of hydraulic measures. Abstract : This paper determined that coal will swell after water soaking, resulting in an increase in volume and a decrease in pore volume. The pore volumes show a logarithmic dependence on soaking time.